Locarno Diplomacy : Germany and the West, 1925-1929 - Jacobson, Jon, 1938- (Book collections on Project MUSE., 1972)
The Locarno Conference of 1925 and the five treaties concluded there have been seen as the turning point of the interwar years, i.e., Germany's acceptance of the 1919 peace settlement and the beginning of a new era of peace. Studying the documentary evidence, much of it available only recently, Jon Jacobson explores the personalities and politics of Locarno and offers a historical interpretation and synthesis of a critical decade in European diplomacy.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.